2013
DOI: 10.1371/journal.pone.0074020
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Serum Iron Is a Potent Biomarker for Spirometric Resistance to Cigarette Smoke among Japanese Males: The Takahata Study

Abstract: Chronic obstructive pulmonary disease is a common disability among elderly subjects with a heavy cigarette smoking habit. In contrast to the population that is susceptible to smoking, in whom pulmonary function worsens with the length of exposure to cigarette smoke, there are elderly individuals whose pulmonary function is not impaired. However, to date, the characteristics of this resistant smoking population have not been investigated. We aimed to identify a biomarker in individuals in whom lung health is ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 22 publications
2
12
0
Order By: Relevance
“…This is comparable to prior investigation which demonstrated that serum ferritin concentration negatively correlated with the FEV 1 /FVC ratio reflecting a positive association of the metal storage protein with airway obstruction 19. Studies have also demonstrated that FVC and FEV 1 can correlate positively with serum ferritin and iron concentrations and transferrin saturation 2022. The disruption in iron homeostasis with cigarette smoking can be associated with oxidative stress, and this can initiate pathways resulting in COPD.…”
Section: Discussionsupporting
confidence: 84%
“…This is comparable to prior investigation which demonstrated that serum ferritin concentration negatively correlated with the FEV 1 /FVC ratio reflecting a positive association of the metal storage protein with airway obstruction 19. Studies have also demonstrated that FVC and FEV 1 can correlate positively with serum ferritin and iron concentrations and transferrin saturation 2022. The disruption in iron homeostasis with cigarette smoking can be associated with oxidative stress, and this can initiate pathways resulting in COPD.…”
Section: Discussionsupporting
confidence: 84%
“…As a potential biological mechanism, it has been suggested that smoking may stimulate erythropoiesis in a dose-related manner due to hypoxia, which is induced by smoking. In addition, hypoxia is likely to suppress hepcidin expression [8919202122]. …”
Section: Discussionmentioning
confidence: 99%
“…Previously, we demonstrated that hyperhomocysteinemia and lower serum iron levels were predictive of a rapid decline in FEV 1 in men who were continuing smokers using the Takahata Study database between 2004-2006 (Visit 1) and 2009 (Visit 2) (n = 147) 16, 19. In 2011 (Visit 3), we re-performed the pulmonary function measurements for 873 participants in this study.…”
Section: Discussionmentioning
confidence: 99%